THE IMPACT OF BEHAVIOURAL PREREQUISITES AND INSTITUTIONS ON THE WELFARE OF COUNTRIES - Gevorgyan, Ruben A.; Gevorgyan, Gayane K. (The journal of contemporary issues in business and government, 2021)
Human behaviour and institutions are two closely linked concepts. Historically, institutions have been created as a mechanism for limiting human behaviour that exists in a particular social environment. At the same time, the established institutions form certain stereotypes of behaviour or so-called accepted norms of behaviour themselves. One of the most important prerequisites for the successful development of society is the harmonisation of formal institutions and accepted norms of behaviour. Inconsistency of formal institutions with accepted norms of behaviour leads to an increase in transactional costs of institutions' functioning, which has a negative impact both on development prospects and on the welfare of countries.In the present article the mechanisms of institutional influence on the accepted norms of behaviour and on the welfare of countries are discussed. The data on traffic accidents are used, which provide information on both the development of institutions and the overall behavioural conditions in different countries. The structural equation model has been applied to a sample of 50 countries and it has been shown that, along with formal institutions, behavioural prerequisites also have a significant impact on countries' welfare. Institutions influence the welfare of countries not only directly, but also through their influence on existing norms of behaviour. At the same time, the model of structural equations with latent variables makes it possible to assess the level of institutions' impact on the welfare of countries through the influence of behavioural prerequisites.